Grupo grande de personas. (UNED, 2023)
Aparece de derecha a izquierda Delia Feoli Chaves; Ana Myriam Shing Sáenz (Secretaria Consejo Universitario); Lucy Chaves; Gustavo Amador; María Isabel Esquivel; Eli Marín; Eddy Solórzano; Joaquín Jiménez